2010
DOI: 10.3357/asem.2748.2010
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Cardiovascular Disease Risk Prediction Model Among Commercial Pilots

Abstract: The application of a 10-yr absolute CVD risk prediction model identified a group of pilots, previously unidentified, who may require a more comprehensive risk assessment. Pilots are continuing to fly commercially beyond the age of 60, which results in substantial increase in the CVD risk burden of the pilot population as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…This aspect of screening has not been investigated in the current study. A new recommendation to licensing authorities in the most recent revision of ICAO Annex 1 Standards and Recommended Practices relating to the content of medical examinations is to increase the emphasis on health education and prevention of ill health ( 15 ). The result from this study is in support of this recommendation to form a health promotion program so that CVD risk scores are properly communicated and understood by airline pilots.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This aspect of screening has not been investigated in the current study. A new recommendation to licensing authorities in the most recent revision of ICAO Annex 1 Standards and Recommended Practices relating to the content of medical examinations is to increase the emphasis on health education and prevention of ill health ( 15 ). The result from this study is in support of this recommendation to form a health promotion program so that CVD risk scores are properly communicated and understood by airline pilots.…”
Section: Discussionsupporting
confidence: 65%
“…However, careful consideration should be taken with regard to the transportability of this risk prediction model and its direct applicability in the regulatory environment. The differences in characteristics from the Framingham sample population, from which the risk assessment model is derived, and lower prevalence of risk factors found in airline pilots than in the general population are among those that should be taken into account ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the Framingham method in 614 pilots certifi ed by the Colombian Civil Aeronautic Society indicated that the prevalence of those in the high risk group (20% or higher 10 yr risk) was 8%, of which 3.7% were found in class 1 certifi cate holders and 13.5% in class 2 certifi cate holders ( 2 ). Application of a nonlaboratory Framingham risk model among commercial pilots, who represented 56% of all Joint Aviation Authority Class 1 certifi cate holders in the UK, showed that 9.2% of all pilots had 10-yr absolute CVD risk greater than 20% ( 13 ). The difference in the prevalence from our study might be due to the difference in the risk factors incorporated in the risk assessment tool.…”
Section: Discussionmentioning
confidence: 97%
“…One of the methods utilized in the cardiovascular screening program is the application of a CVD risk score. This encompasses a risk prediction model to generate an absolute risk of CVD over a particular time frame ( 13 ). The most widely used risk prediction equations have been derived from the Framingham Heart Study ( 1 , 12 ).…”
mentioning
confidence: 99%
“…So prediction and earlier detection of CAD gained importance in aviation medicine and guided studies to identify the pilots at high risk. Houston et al (8) evaluated applicability of 10-year absolute cardiovascular disease (CVD) risk scores which were developed at Framingham Heart Study in a commercial pilot group. They reported that it may identify a group of pilots at high risk who were unidentified previously.…”
Section: Discussionmentioning
confidence: 99%